A travelling wave detector based fault location device and data recorder for medium voltage distribution systems - Jahromi, A.; Wolfs, P.; Islam, Syed (2016)
This paper presents a hardware design for a Travelling Wave (TW) Detector and data recorder for a three phase Medium Voltage (MV) distribution network. The proposed pole mounted platform consists of a capacitively coupled receiver system, a GPS receiver and a Texas Instruments Delfino 28377 processor based travelling wave detection unit. The data recording system uses an Intel Atom base single board computer, a four channel 10Ms/s analogue to digital converter card along with Wi-Fi and GORS communications links. The proposed system is capable of recording three phase voltages simultaneously with the ability to trigger remotely. The platform is mounted in an IP56 enclosure and can be mounted on the MV distribution poles. The paper provides a brief review of hardware and software developed for the TW detector.